Difficulties of Identifying the Early HIV Antibody Seroconversion Period Depending on the Confirmatory Assay - Stefic, Karl (Open Forum Infect Dis, 2020)
BACKGROUND: Identification of HIV infection at the early stage is valuable for patient management, for prevention, and for research purposes. In practice, identification of a recent HIV infection at diagnosis proves challenging after HIV antibody seroconversion but can be suspected using Western blots (WBs) or immunoblots (IBs) as confirmatory assays. METHODS: Five commercially available confirmatory assays were compared using 43 samples from recently infected individuals. This included 2 WBs (New LAV Blot I, Biorad, and HIV Blot 2.2, MP Biomedicals), 2 IBs (INNO-LIA HIV I/II, Fujirebio, and RecomLine HIV-1 & HIV-2, Mikrogen Diagnostik), and 1 immunochromatographic single-use assay (Geenius HIV1/2 supplemental assay, Biorad). RESULTS: Following the manufacturer’s recommendations for interpretation, the 2 WBs led to indeterminate results for 30% and 42% of the samples, suggesting recent infection, compared with 2%–7% for the 3 other assays. When interpreted based on the Fiebig classification, concordant stages were observed in 42% of samples, and only 49% were classified as early seroconversion by all 5 assays. For the remaining specimens, the distinction with chronic infection was highly variable depending on the assay (5%–100%). CONCLUSIONS: Clinical laboratories must consider this variability, which must be kept in mind both for initial diagnosis and for multicenter studies for which inclusion criteria refer to serological profiles by confirmatory assays.